Consumo de tabaco y psicopatología asociada - Becoña, Elisardo; Míguez, Mª Carmen (Psicooncología, 2004)
In the last years, different studies have found a clear relationship between the consumption of tobacco and the presence of other psychopathological disorders, such as depression, anxiety disorders, other addictive disorders (alcoholism, cannabis dependence, cocaine dependence, etc.), attention deficit disorder with hiperactivity and schizophrenia. In this article these relationships are revised and some of the possible explanations to the same ones. We concludes that the presence of psychiatric comorbidity in the smokers supposes a fact of great relevance, as its treatment as for the development of preventive programs. This relevance it will be more important in next years, if it is decreased the number of smokers in the general population. When happening this more difficult to smoking cessation in the smokers with psychopathological disorders. When the smoker don´t have psychopathological disorders they stop more easily to smoke.